2012
DOI: 10.1029/2011jd017080
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nonlocal and local planetary boundary layer schemes in the WRF model

Abstract: [1] A realistic reproduction of planetary boundary layer (PBL) structure and its evolution is critical to numerical simulation of regional meteorology and air quality. Conversely, insufficient realism in the simulated physical properties often leads to degraded meteorological and air quality prognostic skills. This study employed the Weather Research and Forecasting model (WRF) to evaluate model performance and to quantify meteorological prediction differences produced by four widely used PBL schemes. Evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(135 citation statements)
references
References 53 publications
6
119
0
2
Order By: Relevance
“…Both humidity and temperature have an impact on ammonia concentrations. Previous studies suggest that the YSU scheme in WRF [66], which was also applied in our study, tends to overestimate the PBL height [63]. The highest variability between measurements and modelled data are in the midday and are rather constant at night [67].…”
Section: Model Evaluation For the Base And Dynamicmentioning
confidence: 70%
See 1 more Smart Citation
“…Both humidity and temperature have an impact on ammonia concentrations. Previous studies suggest that the YSU scheme in WRF [66], which was also applied in our study, tends to overestimate the PBL height [63]. The highest variability between measurements and modelled data are in the midday and are rather constant at night [67].…”
Section: Model Evaluation For the Base And Dynamicmentioning
confidence: 70%
“…It has been previously shown that PBLH is an important variable for air quality modelling, which is often difficult to simulate accurately in numerical models [62][63]. Determining the PBLH is important in atmospheric numerical models, because it is used in other physical parameterisations and because it is a governing parameter for the distribution of trace gases [64].…”
Section: Model Evaluation For the Base And Dynamicmentioning
confidence: 99%
“…The YSU scheme is typically regarded as one of the better overall performers in intercomparison studies [Hu et al, 2010;Gibbs et al, 2011;Xie et al, 2012;Coniglio et al, 2013;Cohen et al, 2015], though we have done additional testing using five alternative schemes to evaluate how sensitive our results are to a given boundary layer formulation. While there is variability in the magnitude of moisture and temperature change as well as boundary layer height in each set of simulations, the day 1 processes that increase moisture flux into the lower free troposphere appear consistent across most schemes with the exception of MYJ (Fig.…”
Section: Sensitivity To Boundary Layer Schemementioning
confidence: 99%
“…The Yonsei University (YSU) planetary boundary layer (PBL) scheme (Hong et al, 2006) is used in all of the simulations, except one sensitivity experiment that uses the ACM2 (Asymmetric Convective Model with non-local upward mixing and local downward mixing; Pleim, 2007) PBL scheme (referred to as "20km_P7" hereafter, Table 1). Previous studies showed that both the YSU and ACM2 schemes have good performance in simulating boundary layer properties (e.g., Hu et al, 2010;Xie et al, 2012;Cuchiara et al, 2014;Banks and Baldasano, 2016;Banks et al, 2016;Chen et al, 2017). Sub-grid convection, convective transport of chemical constituents and aerosols, and wet deposition from sub-grid convection are parameterized using the Grell 3-D ensemble cumulus scheme (Grell and Devenyi, 2002) in the 20 km simulations, while convective processes are resolved in the 4 km simulations.…”
Section: Model Description and Experiments Setupmentioning
confidence: 99%